CONDITIONS OF HILLING HABITAT OF CHELONIA MYDAS (GREEN TURTLE) IN PANGUMBAHAN BEACH UJUNG GENTENG, SUKABUMI SELATAN - Pertiwi, Meilisha Putri; Lathifah, Suci Siti (Universitas Pakuan, 2018)
Research on the condition of the nesting habitat of Chelonia mydas (green turtle) in Pangumbahan Beach, Ujung Genteng, South Sukabumi has been carried out. Data retrieval is done 6 times for 2 days, 27-28 November 2017 at 3 observation stations. The abiotic parameters measured include surface temperature and depth of 50 cm, surface humidity and depth of 50 cm, beach width, beach slope, and the size of sand grains. While the biotic parameters measured were density, relative density, the frequency of attendance, and distribution patterns of Pandanus tectorius (sea pandanus) vegetation. Based on the results of data processing, the biophysical conditions in Pangumbahan Beach are still suitable for the Chelonia mydas nesting habitat. It also got clear evidence of the many Chelonia mydas landings during the data collection.